2019
DOI: 10.1155/2019/1904565
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study to Reduce the Fracture Pressure of High Strength Rocks Using a Novel Thermochemical Fracturing Approach

Abstract: Current oil prices and global financial situations underline the need for the best engineering practices to recover remaining oil from unconventional hydrocarbon reservoirs. These hydrocarbon reservoirs are mostly situated in deep and overpressured formations, with high rock strength and integrity. Breakdown pressure of the rock is a function of their tensile strength and in situ stresses acting on them. Fracturing stimulation techniques become challenging when treating these types of rocks, and many cases app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 51 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…A scratch test determines the indirect compressive strength of the rock sample called scratch strength. Scratch test has several advantages over conventional UCS tests that include but not limited to minimum sample preparation, nondestructive nature, and higher repeatability. , The detailed discussion about scratch test is reported in our previous publications. In this study, a scratch test was conducted on different Scioto sandstone samples saturated with different solutions of clay stabilizers. After flooding with surfactants and commercially available clay stabilizers, the samples were dried before performing a scratch test.…”
Section: Methodsmentioning
confidence: 99%
“…A scratch test determines the indirect compressive strength of the rock sample called scratch strength. Scratch test has several advantages over conventional UCS tests that include but not limited to minimum sample preparation, nondestructive nature, and higher repeatability. , The detailed discussion about scratch test is reported in our previous publications. In this study, a scratch test was conducted on different Scioto sandstone samples saturated with different solutions of clay stabilizers. After flooding with surfactants and commercially available clay stabilizers, the samples were dried before performing a scratch test.…”
Section: Methodsmentioning
confidence: 99%
“…This reaction is normally considered a green reaction because it is mainly composed of salts [ 40 , 41 ]. Due to the high-pressure temperature generation, thermochemical fluids were successfully used in the oil and gas industry for several purposes such as wax removal [ 42 ], heavy oil production [ 43 ], breakdown pressure reduction [ 44 , 45 , 46 ], increasing stimulated reservoir volume [ 47 ], and enhanced oil recovery (EOR) applications [ 48 ]. Mahmoud [ 23 ] used thermochemical fluids along with chelating agents to remove the filter cake formed by barite-weighted drilling fluids in oil- and water-based types.…”
Section: Methodsmentioning
confidence: 99%
“…The lithology of HDR reservoir is mainly igneous rock, such as granite, which generally has a higher breakdown pressure than conventional reservoir. For the purpose of reducing breakdown pressure, several novel fracturing technologies, such as cyclic hydraulic fracturing, thermochemical fracturing and thermochemical acid fracturing were proposed [ [8] , [9] , [10] ]. Some investigations also indicated that the breakdown pressure of hard rock could be reduced significantly by improving the temperature difference between injected fluid and rock [ 11 ].…”
Section: Introductionmentioning
confidence: 99%